François Poullain de la Barre : filósofo feminista y cartesiano sui generis - León, Luz Stella (ENDOXA, 2011)
Este artículo trata de introducir brevemente la vida y obra de François Poullain de la Barre, filósofo feminista y cartesiano sui generis del siglo XVII, dando a conocer la deriva social de los principios cartesianos. This article briefly introduces the life and work of François Poullain, feminist philosopher and 17th century sui generis Cartesian, announcing the social drift of Cartesian principles.